IJSCOL 2020
DOI: 10.35631/ijscol.11001
|View full text |Cite
|
Sign up to set email alerts
|

Lean Manufacturing Adoption in Malaysia: A Systematic Literature Review

Abstract: The purpose of this paper is to perform a systematic literature review (SLR) on lean manufacturing (LM) adoption in Malaysia while highlighting research trends and gaps from this literature. The SLR involved analysing 163 scholarly articles from international journals and conference proceedings published between the year 2005 to 2019. The articles are classified as literature review, conceptual paper, case study, and survey research. These articles were also grouped into nine meaningful research themes, named:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…The percentage of research methods used to investigate the LM implementation in SMEs by Alkhoraif et al (2019) showed that multiple case studies and mixed-methods only consisted of 11% and 7%, respectively, as compared to the single case study (34%) and survey (30%). Osman et al (2020) presented that most literature on LM research in Malaysia were empirical articles, mostly with survey studies (42%) as compared to mixed methods (2%). Therefore, convergent parallel mixed-methods (qualitative and quantitative) research was employed in the case of the three M&E companies to provide a comprehensive analysis of the research problems and increase the accuracy of the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of research methods used to investigate the LM implementation in SMEs by Alkhoraif et al (2019) showed that multiple case studies and mixed-methods only consisted of 11% and 7%, respectively, as compared to the single case study (34%) and survey (30%). Osman et al (2020) presented that most literature on LM research in Malaysia were empirical articles, mostly with survey studies (42%) as compared to mixed methods (2%). Therefore, convergent parallel mixed-methods (qualitative and quantitative) research was employed in the case of the three M&E companies to provide a comprehensive analysis of the research problems and increase the accuracy of the results.…”
Section: Methodsmentioning
confidence: 99%
“…They are expecting to grow at an average annual growth rate of 4.1 per cent to reach RM 43 billion in 2020 (MIDA, 2019). However, the existing literature on LM adoption for M&E in Malaysia only amounts to 2.3%, which is very little as compared to the automotive industry with 37.1% (Osman et al, 2020). Therefore, this study aimed to explore the predominant critical success factors (CSFs) of LM in M&E manufacturing SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Hall (1977) stated awareness as “the lack of concern expressed by an individual regarding a product and services.” Moreover, the halal food market is regarded as a fruitful business, and there in Muslim and non-Muslim countries, it has become a significant concern (Osman et al ,2020). Similarly, awareness is essential for customer behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rogers (2003) stated that PCT implies how far an innovation is observed and how challenging it is to use? Osman et al (2020), in their study linked to HSCA, revealed that today's halal concept is beyond the understanding of religious values,…”
Section: Perceived Relative Advantagementioning
confidence: 99%
“…From the perspective of operations research, Mohd Yusof and Aspinwall (2000) asserted that a model answers the question 'what is', whereas, a framework answers the question 'how to'. In the same vein, Osman, Othman, and Abdul Rahim (2020b) perceived a model as a graphical respresentation of statistical assessment on relationship between variables from survey studies, and a framework represent a complete plan of implementation (i.e. roadmap), established usually based on case study method.…”
Section: About Models and Frameworkmentioning
confidence: 99%